Dario kajal, a new species of badid fish from Meghalaya, India (Teleostei: Badidae) - Britz, Ralf; Kullander, Sven O (Zootaxa, 2013)
Dario kajal, new species, is described from Seinphoh stream in the Jaintia Hills of Meghalaya, India. It can be distinguished from all other congeners by the presence of a postorbital stripe that continues behind the eye in line with the preorbital stripe and by the presence in males of a series of double bars restricted to the upper half of the body. The discovery of D. kajal in the Meghna River drainage raises the number of Dario species to five and raises interesting questions about the biogeography of the genus.